The influence of classroom based assessment and communicative approach in teaching-learning English for Indonesian learners - Idaryani Idaryani (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
Indonesia is archipelago country and consists of hundreds different ethnic groups who speak more than seven hundred vernacular languages. Generally, Indonesian people are bilingual. They speak vernacular languages as their mother tongues and Bahasa Indonesia as means of  communication among different ethnic groups.  English is spoken as additional or foreign language. Since English is not means of communication for learners in their daily life, it will be very challenging for them in learning process moreover English is only learnt as prerequisite subject in many schools. It is believed that the implementation of Classroom Based Assessment (CBA) methods  and communicative language teaching (CLT) in teaching-learning will encourage students in learning English. It is also expected that the method will enable the students to be more engaged during classroom activities. Since the assessment methods will evaluate and assess all learners’ performances. The implementation of CBA and communicative approach of teaching is also expected to make learning English more interesting for learner so the learner will be aware that learning English can be as a fun activities. Communicative approach will enable students to be more active and enable them to do more interesting activities through speaking rather than sitting and listening to the teachers. The activities such as presentation, role play, and storytelling about attractive topics are expected to be more interested for students in teaching-learning process.